2014
DOI: 10.1179/1743288x14y.0000000139
|View full text |Cite
|
Sign up to set email alerts
|

Yoga for pain and sleep quality in rheumatoid arthritis: study protocol for a pilot randomized controlled trial

Abstract: Background: Yoga is a popular complementary and alternative medicine (CAM) therapy among people with rheumatoid arthritis (RA), perceived as offering self-management options for physical and psychosocial symptoms associated with RA. Objectives: The primary aims of the current pilot study are (1) to assess the feasibility and safety of a relaxation-focused yoga intervention tailored for people with RA and (2) to estimate the effect of yoga on RArelated pain, sleep quality, functional disability, disease activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…A total of 4382 participants were included (sample size ranged from 20 [ 66 ] to 490 [ 46 ] participants). Participant ages ranged from 18 [ 27 , 32 , 33 , 36 , 38 , 45 , 55 , 67 , 70 ] to 87 years [ 22 ]. The majority of participants were female ( n = 3431) [ 21–70 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 4382 participants were included (sample size ranged from 20 [ 66 ] to 490 [ 46 ] participants). Participant ages ranged from 18 [ 27 , 32 , 33 , 36 , 38 , 45 , 55 , 67 , 70 ] to 87 years [ 22 ]. The majority of participants were female ( n = 3431) [ 21–70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interventions included strengthening exercise ( n = 26) [ 21 , 23–25 , 27 , 30 , 31 , 35 , 36 , 38 , 42 , 43 , 45–48 , 50 , 51 , 54 , 55 , 58 , 59 , 61 , 63 , 64 , 68 ], aerobic exercise ( n = 17) [ 21 , 23–25 , 27 , 29 , 36 , 38 , 44 , 45 , 47 , 55 , 59 , 61 , 63 , 64 , 68 ], flexibility exercises ( n = 10) [ 25 , 30 , 31 , 35 , 36 , 46 , 51 , 54 , 63 , 64 ], yoga ( n = 8) [ 37 , 39–41 , 52 , 56 , 62 , 67 ], walking ( n = 5) [ 30 , 36 , 57 , 69 , 70 ], hydrotherapy ( n = 4) [ 26 , 27 , …”
Section: Resultsmentioning
confidence: 99%
“…A detailed study protocol has been previously reported (Ward, Stebbings, Athens et al, ), and is summarized below. The study was registered with the Australian New Zealand Clinical Trials Registry (ACTRN12612001019897), received ethical approval from the Southern Health and Disability Ethics Committees (Ref 12/STH/24) and Health Research South (ID00837), and was conducted in accordance with the 1964 Declaration of Helsinki and its later amendments.…”
Section: Methodsmentioning
confidence: 99%
“…Participants allocated to the yoga group continued with their usual medical care provided by their rheumatologist and general practitioner. Additionally, they commenced an 8‐week programme of group and home yoga practice (Ward, Stebbings, Athens, et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…'Adherence to home practice in the previous week was verbally reported to the yoga instructor at the beginning of each session, and barriers and adherers to home practice were discussed among the group.' 22…”
Section: Explanationmentioning
confidence: 99%